Early parenting intervention accelerates inhibitory control development among CPS-involved children in middle childhood: A randomized clinical trial - Korom, Marta (Dev Sci, 2020)
Children at risk for neglect or abuse are vulnerable to delays in inhibitory control development. Prior findings suggest that early parenting interventions that target parental sensitivity and responsiveness during infancy can improve executive function outcomes of high-risk children during preschool years; however, little is known about how persistent these gains are through middle childhood. Participants included 76 CPS-involved children who were randomly assigned to either the ABC intervention (N = 32) or the Developmental Education for Families (DEF) control intervention (N = 44), and 53 low-risk children. Children completed the Stop Signal Reaction Time (SSRT) paradigm at ages 8 and 10. Intervention group predicted performance on the SSRT at age 8 such that children who received the ABC intervention and children in the low-risk group performed significantly better than children who received the DEF intervention (ABC vs. DEF: Cohen’s d = 0.92; low-risk group vs. DEF: d = 0.56). The performances of the ABC and the low-risk groups were not statistically different. There were no significant group differences in SSRT performance at age 10. These findings demonstrate that the ABC intervention has long-term beneficial effects on inhibitory control development in children with a history of early caregiving adversity.